(untitled) (Advancements in Homeopathic Research, 2022)
Background: Over the past several decades, researchers have learned a lot about the twelve tissue remedies. The use of homoeopathic preparation in agriculture has started recently. But still further research is needed to help a large population in agricultural field. Twelve tissue remedies help in increasing the plant growth and productivity. Objective: To assess the effectiveness of twelve tissue remedies and five phos 6X on root knot nematode Meloidogyne incognita in tomato. Materials and Methods: The study was carried out at The Tamilnadu Agricultural University, coimbatore, tamilnadu, during the month of August 2021. The experiment was conducted under glass house conditions. Earthen pots of five kg capacity were autoclaved for 12 hours, filled with pot mixture of red earth, sand and Farm Yard Manure (1:1:1) and tomato seedlings of variety Periyakulam (PKM) 1 were raised in each pot replicated thrice. Ten days after germination, each pot was inoculated with 2 egg massesper Pot. After 15 days of inoculation, a five milligram of commercially available tissue remedies diluted in 30ml of water was applied in daily dose for 45days. After 45 days of application, the experiment was terminated and the observations were recorded on plant growth parameters and nematode infestations. Results: It was observed that the 12 tissue remedies were found to be superior in suppressing the nematode population. Among the tissue remedies, Silicea 6x was found to be superior in reducing the nematode population. Conclusion: The result obtained from this preliminary study suggests that the twelve tissue remedies help in agricultural purpose. The use of homoeopathic preparation in agriculture has started recently. Homoeopathic preparations are being used efficiently for increasing active principles in medicinal plants, plant detoxification for metals such as aluminium and copper, increasing plant growth rate and productivity, plant metabolism and control of disease. Further detailed investigations required from other plant sources also.